Microstructure and temperature-dependence of Raman scattering properties of β-(AlxGa1-x)2O3 crystals. (April 2020) - Chen, Xian; Niu, Wenlong; Wan, Lingyu; Xia, Changtai; Cui, Huiyuan; Talwar, Devki N.; Feng, Zhe Chuan
Abstract: Bulk crystals of β-Ga2 O3, (Al0.1 Ga0.9 )2 O3 and (Al0.2 Ga0.8 )2 O3 were grown by the optical floating zone and edge-defined film-fed methods. Their microstructure and temperature-dependent phonon characteristics were investigated systematically by using high resolution X-ray diffraction (HR-XRD) and Raman scattering spectroscopy. HR-XRD results revealed a very good crystalline phase for all the samples. As compared to the pure β-Ga2 O3, the interplanar spacings in (Al0.1 Ga0.9 )2 O3 and (Al0.2 Ga0.8 )2 O3 samples are found decreasing with the increase of Al contents – exhibiting distorted lattice structures. Due to the deformations in (Alx Ga1-x )2 O3, the Raman peaks revealed redshifts and linewidth broadening as the Al composition (x) is increased. The lattice distortion mainly affected the Raman modes in the range of less than 600 cm −1 and had a relatively trivial effect on the modes higher than 600 cm −1 . With the increase of temperature, the Raman peaks are also redshifted and linewidth broadened. Similar to a pure β-Ga2 O3, our Raman shifts in the two (Alx Ga1-x )2 O3 crystals revealed quadratic dependence on temperature – showing specific relationships. However, the temperature dependent widening of the Raman active phonons in (Alx Ga1-x )2 O3 exhibited a convoluted behavior different from β-Ga2 O3 . The results are significant for further understanding of (Alx Ga1 - x )2 O3 crystals and evaluating its use in device applications. Highlights: Al-alloying induced lattice deformation in β-Ga2 O3 is analyzed quantitatively. For (Alx Ga1-x )2 O3 (x = 0, 0.1, 0.2) crystals the Raman modes are measured systematically. The dependent properties of Raman shifts and linewidths on Al-alloying and temperature are obtained.